17beta-hidroksisteroid-dehidrogenaze - obetajoče farmakološke tarče - Kristan, Katja (Farmacevtski vestnik, 2005)
The 17beta-hydroxysteroid dehydrogenases (17beta-HSDs) have important roles inthe regulation of steroid hormone actions through their catalysis of the oxidation or reduction of estrogens and androgens at position 17. To date, 11 different human 17beta-HSDs have been described Dysfunction of the human 17beta-HSDs results in reproduction disorders and neuronal diseases, and in the development of hormonedependent cancers. This review summarizes current knowledge on the medical implications of the 17beta-HSDs and presents some representative inhibitors of the different 17beta-HSD isozymes.
Keywords: androgeni; biosinteza; estrogeni; hormoni; inhibitorji